KAIZEN DAN IMPLEMENTASINYA TERHADAP FAKTOR-FAKTOR YANG MENINGKATKAN KINERJA KARYAWAN PERUSAHAAN - Boma Jonaldy; Nur Anisah (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
Kaizen is one of the company's strategies in increasing business productivity. In addition to being related to production management, kaizen is also related to human resource management. This can be in line with increase in employee performance. The implementation of kaizen on the factors of improving employee performance can not necessarily be done instantly, there needs to be a thorough adaptation that takes a long time to implement. In case, the researchers try to examine "Kaizen and its Implementation of Factors That Improve Company Employee Performance" through literature studies from various sources such as articles, books, and scientific journals. It was found that there are various point of performance improvement in the implementation of kaizen in a company. Not all factors can match one company to another. The implementation of kaizen that not all can be applied to the company also requires adjustments. This research is expected provide knowledge about kaizen & employee performance for all readers.